How Does the Bridge Design Affect the Behavior of Pedestrian Bridge Users?: A Case Study in Pandanaran Skybridge Corridor Semarang - Djoko Indrosaptono; Hening Triastity (Research Horizon, 2021)
Skybridge can be considered as a corridor space because it connects one place to another. One of which is the Pandanaran Skybridge which connects the parking building with the Pandanaran souvenir center area in the downtown of Semarang City, Indonesia. This study attempts to analyze the effect of skybridge planning on user behavior with a case study in the Pandanaran Semarang skybridge corridor. The Semarang City Government made these public facilities to cope with traffic flow and the need for parking spaces. This building is fairly new because it was completed in 2020, therefore the Pandanaran Skybridge needs to be reviewed. The study begins by studying the understanding and standards of pedestrian bridges, the factors that affect crossings, physical and non-physical views of buildings, as well as visitor perceptions of Skybridges. The architectural design approach is design recommendations based on user needs and convenience. In conclusion, there are things that need to be improved on the Pandanaran Skybridge along with design recommendations.